The Neuronal Ceroid Lipofuscinoses: A Case-Based Overview - Grisolia, Michele; Sestito, Simona; Ceravolo, Ferdinando; Invernizzi, Federica; Salpietro, Vincenzo; Polizzi, Agata; Ruggieri, Martino; Garavaglia, Barbara; Concolino, Daniela (Journal of Pediatric Biochemistry, 2016)
The neuronal ceroid lipofuscinoses (NCLs) are a heterogeneous group of inherited, progressive neurodegenerative diseases. Manifestations may begin between the neonatal period and young adulthood, depending on the various subtypes. The different phenotypes are similar and include visual loss, seizures, loss of motor and cognitive function, and early death. At autopsy, there is massive neuronal loss with characteristic storage in the remaining neurons. Neurons appear to die because of increased rates of apoptosis and altered autophagy as occurs in lysosomal storage diseases. A total of 13 neuronal ceroid lipofuscinoses (CLN) genetic forms have been identified so far (CLN type 1–14). In the present review, we propose a classification scheme of the major forms and report the case of a familial recurrence of NCL type 10, with a mutation in the CLN10 gene coding for the cathepsin D protein.
Keywords: neuronal ceroid lipofuscinosis; neurodegenerative diseases; CLN10